Preparation and Complex Characterisation of Stabilised Gold Nanoparticles: Biodistribution and Application for High Resolution In Vivo Imaging - Jaroslav Turánek; Pavlína Turánek Knötigová; Pavel Kulich; Radim Skoupý; Kamila Hrubanová; Naděžda Vaškovicová; Ladislav Fekete; Antonín Kaňa; Robert Mikulík; Milan Raška (Pharmaceuticals, 2024)
The Turkevich method was optimized to prepare gold nanoparticles (AuNP) stabilized by polyethyleneglycol (PEG) for µCT. Using various independent modalities, we thoroughly characterized the optimized PEG-AuNPs. Here, we show that PEG-AuNPs are retained in the blood and provide a high contrast in the high-resolution µCT imaging of blood vessels and inner organs. The biodistribution is characterized by prolonged circulation in the blood and accumulation in the liver, spleen and skin. The accumulation of AuNP in the skin resulted in the blue discoloration of eyes and the whole skin. In vitro experiments using a leukemic monocyte THP-1 cell line model expressing high levels of NLRP3 demonstrated that the NLRP3inflammasome was not activated by PEG AuNP. Over 9 months, the mice were scanned by µCT and were in good health. Scans in mice using PEG-stabilized AuNPs in this study were sharper, with a higher contrast, when compared to a commercial contrasting agent at the same dose. The PEG-AuNPs were morphologically and chemically stable for at least two years when stored in the refrigerator.